The Influence of Principal’s Leadership on Students’ Sports Achievement (A Case Study at SMAN Keberbakatan Olahraga, Bengkulu Province) - Jesicha Fitria Larasati; Harius Eko Saputra; Maryaningsih Maryaningsih (Universitas Dehasen Bengkulu, 2026)
This study aims to examine the influence of principal’s leadership on students’ sports achievement at SMAN Keberbakatan Olahraga, Bengkulu Province. The research employed a quantitative descriptive method using a survey approach. Data were collected through questionnaires and documentation involving 76 student respondents selected as the sample from a total population of 138 students. The independent variable in this study was the principal’s leadership, while the dependent variable was students’ sports achievement. Data were analyzed using simple linear regression to determine the relationship and influence between the variables. The results of the study indicate that the correlation coefficient (R) between the principal’s leadership and students’ sports achievement is 0.721, which falls into the strong category. The coefficient of determination (R²) shows that 52.0% of students’ sports achievement is influenced by the principal’s leadership, while the remaining 48.0% is explained by other factors not examined in this study. Furthermore, the t-test results confirm that the principal’s leadership has a significant effect on students’ sports achievement. These findings highlight the crucial role of leadership in fostering student potential and improving performance in sports education. The study suggests that strengthening leadership strategies can further enhance students’ achievements at sports-focused schools.